Twentieth Century Milestones in Tamil Nadu Forestry - Sekar, T. (Indian Forester, 2000)
This paper describes the salient aspects of four noteworthy achievements in the field of production forestry in Tamil Nadu State during the twentieth century. A brief background about tbe silvicultural practices relating to the river fringe and canal bank plantations, Wattle and Blue gum plantations in the hills, cultivation of Tea and Rubber and tank-foreshore plantations are presented in the paper.